2019
DOI: 10.1130/b35036.1
|View full text |Cite
|
Sign up to set email alerts
|

U-Pb and oxygen isotope characteristics of Timanian- and Caledonian-age detrital zircons from the Brooks Range, Arctic Alaska, USA

Abstract: The Devonian connection between the Brooks Range of Alaska, USA, with the continental margin of Arctic Canada and its subsequent Jurassic–Cretaceous counterclockwise rotation to form the Amerasian Basin, is a highly debated topic in Arctic tectonics. This resource-rich region was assembled from terranes that formed part of Laurentia or Baltica, or were juvenile oceanic arcs in the early Paleozoic that were brought together during Caledonian Orogenesis and the subsequent collision that formed Pangea (Uralide Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Due to the presence of ca. 500-740 Ma igneous rocks and abundant detrital zircons in metasedimentary units of the southwestern subterranes of the Arctic Alaska-Chukotka microplate [69,140,[148][149][150][151] this composite terrane is often invoked as a source of Neoproterozoic detritus to the Ellesmerian clastic wedge [8,[137][138][139] (Figure 13(c)). The presence of these Cryogenian-Ediacaran igneous ages and the similarities in provenance to portions of northern Baltica led to the proposed restoration of the Arctic Alaska-Chukotka microplate adjacent to the ca.…”
Section: Age and Provenance Of The Darcy Creek Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the presence of ca. 500-740 Ma igneous rocks and abundant detrital zircons in metasedimentary units of the southwestern subterranes of the Arctic Alaska-Chukotka microplate [69,140,[148][149][150][151] this composite terrane is often invoked as a source of Neoproterozoic detritus to the Ellesmerian clastic wedge [8,[137][138][139] (Figure 13(c)). The presence of these Cryogenian-Ediacaran igneous ages and the similarities in provenance to portions of northern Baltica led to the proposed restoration of the Arctic Alaska-Chukotka microplate adjacent to the ca.…”
Section: Age and Provenance Of The Darcy Creek Formationmentioning
confidence: 99%
“…These early Paleozoic U-Pb age populations are abundant in strata of the Ellesmerian clastic wedge (Figure 13(c); [8,[137][138][139]), as well as the Clarence River Group of the North Slope subterrane (e.g., [20]) and a wide variety of Devonian(?) metasedimentary units throughout the southwestern subterranes of the Arctic Alaska-Chukotka microplate (e.g., [35,69,151]). The Ordovician-Silurian signature reflects ties to arc magmatism in the circum-Arctic realm, which is locally preserved in the Pearya terrane [162], Doonerak arc of the Arctic Alaska-Chukotka microplate ( [35] and references therein), and the Descon Formation of the Alexander terrane (e.g., [163,164]).…”
Section: Age and Provenance Of The Darcy Creek Formationmentioning
confidence: 99%
“…3a and 3b) (Fig. 3a and 3b;Hitzman 1983Hitzman , 1986Hitzman et al 1986;Till et al 2008;Rohr et al 2018;Robinson et al 2019).…”
Section: Introductionmentioning
confidence: 97%
“…Our interpretations focus on (1) the first-order controls on the flow, pulses, and redox evolution of mineralizing basinal brines, and (2) the specific metal endowment of the RCB deposit in critical metals (e.g., Co, Ge, Ni) as a consequence of the breakdown of metal-rich algal-bacterial organic matter during dolomitization and sulfide mineralization. The Scandian phase of the northern evolution of the Caledonian orogeny marked the final collision between Baltica and Laurentia (Miller et al 2011;Gee et al 2013;Robinson et al 2019;Fig. 3a).…”
Section: Introductionmentioning
confidence: 99%
“…Gehrels, inhouse program at Arizona LaserChron Center) and (C) Shepard plot(Saylor et al, 2017) of U-Pb data shown in Fig.2Aof the text. U/Pb and Hf data is from select Arctic and northern Cordilleran terranes including the Svalbard terranes(Pettersson et al, 2009(Pettersson et al, , 2010Gasser and Andresen, 2013;Beranek et al, 2020); Franklinian basin(Beranek et al, 2013a;Hadlari et al, 2014;Dewing et al, 2019); Pearya terrane(Hadlari et al, 2014;Beranek et al, 2015;Malone et al, 2014Malone et al, , 2019Estrada et al, 2018;Dewing et al, 2019; Beauchamp et al, 2019); Canadian Arctic Islands clastic wedge(Anfinson et al, 2012a, b); Arctic Alaska terrane including the North Slope subterrane(Macdonald et al, 2009;Strauss et al, 2013Strauss et al, , 2017Strauss et al, , 2019aGottlieb et al, 2014;McClelland et al, 2015;Cox et al, 2015;Johnson et al, 2016;Lane et al, 2016;Colpron et al, 2019), Seward Peninsula (Amato et al, 2009Till et al, 2014;Dumoulin et al, 2018a), Southwestern subterranes(Strauss et al, 2017;Hoiland et al, 2017;Robinson, et al, 2019), Doonerak(Strauss et al, 2017) and Whale Mountain Allochthon(Johnson et al, 2016(Johnson et al, , 2018Strauss et al, 2019b); Farewell and Mystic terranes(Bradley et al, 2014;Malkowski et al, 2014; Dumoulin et al, 2018a, b); Alexander terrane(Beranek et al, 2013b,c; Tochilin et al, 2014; White et al, 2016); and Yukon-Tanana terrane in southeastern Alaska…”
mentioning
confidence: 99%